Chitosan-based nanoparticles of Moringa oleifera with enhanced bioactivities - FATMA HUSSAIN; ABEER KHIZRAN; MUNIBA KARAMAT; JAVARIA HAFEEZ (Kashmir Journal of Science)
Moringa oleifera is also known as miracle tree because of it’s nutritional and physiological benefits. In this research, structural and biochemical characterization of Moringa oleifera’s extracts and nanoparticles were done. n-hexane, methanolic and aqueous extract of M. oleifera was prepared by microwave assisted method. The obtained percentage yield of methanolic extract was the highest (8.86%). Chitosan based nanoparticles of methanolic extract was prepared by ionic gelation method that was almost 100nm in size with positive charge on it. Biochemical characterization was assessed by antioxidant (total phenolic content, total flavonoid content and DPPH radical scavenging assay), anti-diabetic (alpha amylase inhibition assay), cytotoxic (percentage hemolysis) and anti-inflammatory (albumin denaturation method) activities. One-way ANOVA was used for the analysis of data. In comparison between extracts and nanoparticles, it was observed that nanoparticles were less toxic (1.99±0.86%) and showed higher antioxidant (65.67±0.26%), anti-diabetic (85.87±6.64%) and anti-inflammatory potential (83.55±0.76%). Different functional groups were identified by fourier transform infrared spectroscopy such as primary and secondary amines, amides, carboxylic acid, alkanes, aldehyde, alkene, alcohol, ether, ester and sulphates. High performance liquid chromatography confirmed the presence of kaempherol, p-coumaric acid, salicylic acid and chlorogenic acid.